Über das Anwachsen ganzer transzendenter Lösungen einer Differentialgleichung - Strelitz, S. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ш. Стрелиц. О росте целых трансцендентных решений дифференциальных уравненийŠ. Strelicas. Diferencialinių lygčių sveikų trancendentinių sprendinių augimo klausimu